2013
DOI: 10.1155/2013/636287
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Mitochondrial Morphology by Autophagy and Its Role in High Glucose Effects on Chronological Lifespan ofSaccharomyces cerevisiae

Abstract: In Saccharomyces cerevisiae, mitochondrial morphology changes when cells are shifted between nonfermentative and fermentative carbon sources. Here, we show that cells of S. cerevisiae grown in different glucose concentrations display different mitochondrial morphologies. The morphology of mitochondria in the cells growing in 0.5% glucose was similar to that of mitochondria in respiring cells. However, the mitochondria of cells growing in higher glucose concentrations (2% and 4%) became fragmented after growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Previous studies have demonstrated that autophagy has an important role in maintaining proper mitochondrial function and dynamics since autophagy-defective mutants present severe mitochondria dysfunctions 57 58 . In particular, the regulation of the mitochondrial membrane potential appears to be crucial to regulate autophagic flux.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that autophagy has an important role in maintaining proper mitochondrial function and dynamics since autophagy-defective mutants present severe mitochondria dysfunctions 57 58 . In particular, the regulation of the mitochondrial membrane potential appears to be crucial to regulate autophagic flux.…”
Section: Resultsmentioning
confidence: 99%
“…Since mitochondria are both the targets for oxidative stress and as a rich source of ROS (Burtner et al 2009; Aung-Htut et al 2013), we hypothesized that mitochondrial dysfunction could be involved in arsenic nephrotoxicity. We found that arsenic exposure led to altered mitochondrial morphology (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of mitochondria to the production of ROS in the skin is only substantial in the stem cells, but further on is small compared to other organs, because during the cornification process the keratinocytes degrade all their organelles including the nucleus, mitochondria, peroxisomes, and the endoplasmic reticulum [ 80 , 81 ]. The importance of mitochondria in the aging process independently of the production of ROS is summarized elsewhere [ 82 , 83 , 84 ].…”
Section: Ros Production In the Skinmentioning
confidence: 99%